2019
DOI: 10.3390/geosciences9120499
|View full text |Cite
|
Sign up to set email alerts
|

Late Orogenic Heating of (Ultra)High Pressure Rocks: Slab Rollback vs. Slab Breakoff

Abstract: Some (ultra)high-pressure metamorphic rocks that formed during continental collision preserve relict minerals, indicating a two-stage evolution: first, subduction to mantle depths and exhumation to the lower-crustal level (with simultaneous cooling), followed by intensive heating that can be characterized by a β-shaped pressure–temperature–time (P–T–t) path. Based on a two-dimensional (2D) coupled petrological–thermomechanical tectono-magmatic numerical model, we propose a possible sequence of tectonic stages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 101 publications
2
25
0
Order By: Relevance
“…Figure 1B illustrates a simplified schematic clockwise pressure-temperature (P-T) path for material following a typical particle path of shallow-dipping underthrusting and subvertical uplift (e.g., Likhanov, 2020). However, P-T paths of deeply subducted rocks commonly indicate more complicated multiphase burial and exhumation histories (e.g., Angiboust et al, 2018;Sizova et al, 2019). Sediments accreted at the wedge front may also experience elevated pressures and temperatures when further incorporated in the wedge body, but they show a distinct difference in the relative timing between thrusting and peak metamorphism (van Gool and Cawood, 1994): basal accretion occurs at peak metamorphic conditions, while peak metamorphism postdates thrust imbrication related to frontal accretion ( Fig.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Figure 1B illustrates a simplified schematic clockwise pressure-temperature (P-T) path for material following a typical particle path of shallow-dipping underthrusting and subvertical uplift (e.g., Likhanov, 2020). However, P-T paths of deeply subducted rocks commonly indicate more complicated multiphase burial and exhumation histories (e.g., Angiboust et al, 2018;Sizova et al, 2019). Sediments accreted at the wedge front may also experience elevated pressures and temperatures when further incorporated in the wedge body, but they show a distinct difference in the relative timing between thrusting and peak metamorphism (van Gool and Cawood, 1994): basal accretion occurs at peak metamorphic conditions, while peak metamorphism postdates thrust imbrication related to frontal accretion ( Fig.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It is no different in the Cyclades. The Cycladic archipelago preserves the results of the destruction of an extensive terrane stack that extended from the Hellenides in Greece to the Taurus Mountains in Turkey (Gautier and Brun, 1994a, b;Kempler and Garfunkel, McKenzie, 1977;Taymaz et al, 1991). The debate as to the nature of exhumation processes will not be resolved by a sole focus on the Cycladic eclogite-blueschist belt, as demonstrated in this paper.…”
Section: Tectonic Implicationsmentioning
confidence: 89%
“…Such effects were not observed in the Cyclades. Sizova et al (2019) also showed the "peeloff" model (Brun and Faccenna, 2008) to be unlikely in the Aegean region.…”
Section: Tectonic Implicationsmentioning
confidence: 95%
“…Although the slab-peel model is consistent with enhanced heat flow during crustal stretching after the accretion event, Lister and Forster (2009) show that such a model requires the asthenosphere to be uplifted to sufficiently shallow levels that a period of major basaltic volcanism would have taken place, with volumes comparable to those observed in some large igneous provinces. Sizova et al (2019) also showed the "peel off" model (Brun and Faccenna, 2008) to be unlikely.…”
Section: Tectonic Implications 310mentioning
confidence: 99%